Doing and Negotiating Transgender on the Front Line: Customer Abuse, Transphobia and Stigma in the Food Retail Sector. (October 2021) - Hadjisolomou, Anastasios
Despite growing research on LGBT+ populations, few studies have examined transgender individuals' specific workplace experiences, whose voice is often subsumed in a wider category. This article presents the story of Kathrine, a female transgender food retail worker, and discusses the abusive, discriminatory and transphobic behaviour of customers, which has received limited attention in the sociology of service work literature. The article reveals the stigmatization of transgender employees by customers, which is expressed through micro-aggressions, such as mis-gendering, mocking and harassing, and is often neglected and/or tolerated by management. Kathrine discusses the coping strategies she utilizes to reduce the negative consequences of the stigma, and to negotiate and protect her gender identity. These include confronting and/or refusing to serve transphobic customers, reflecting her resilience towards discrimination and abuse. The article calls for further research to understand transgender service employees' experiences and the complexity and diversity of coping strategies used by stigmatized workers.